How People Evaluate Anti-Corona Measures for Their Social Spheres: Attitude, Subjective Norm, and Perceived Behavioral Control - Godbersen, Hendrik; Hofmann, Laura Anna; Ruiz-Fernández, Susana (Frontiers in Psychology, 2020)
Restrictions on outdoor activities, tips for hygiene and tips for mental health are amongst the most common initiatives to counter the COVID-19 pandemic. These measures aim to protect people’s health and, on the same time, impact their social lives. So far, it is little known how people evaluate those anti-Corona measures with regards to their social spheres (close family, wider family and friends, colleagues, and society). Furthermore, it is plausible that the subjective evaluation of attitudinal objects and especially severe events, like the COVID-19 pandemic and the related counter-measures, is multi-dimensional. Against this background, we combine the social spheres with the elements of the Theory of Planned Behaviour. On the methodological basis of the Means-End Theory of Complex Cognitive Structures, we determine the perceived relevance and quality of the attitude, subjective norm, perceived behavioural control, and social spheres regarding anti-Corona measures. Furthermore, the applied methodology allows the deduction of norm strategies to define the priority of securing or increasing the effectiveness of elements of anti-Corona measures. Based on the answers of 663 participants, we found that the protection from COVID-19 and its consequences (attitude) are more important to people than the practicability of anti-Corona measures in their social lives (perceived behavioural control), which, again, has a higher subjective relevance than the willingness to fulfil the expectations of others (subjective norm). Additionally, people distinguish between their close family (higher subjective relevance) and their other social spheres (lower subjective relevance). The people attribute the highest quality to the tips on hygiene, followed by the restrictions on outdoor activities and the tips for mental health. The protection and practicability of the anti-Corona measures have higher quality ratings than the willingness to fulfil the expectations of others. Based on the norm strategies, policy makers should secure the effectiveness of the current anti-Corona measures with a high priority by focusing on the protection and practicability with regards to close and wider family and friends. Increasing the effectiveness of the protection and practicability of anti-Corona measures in work and society also has a high priority. Focussing on the subjective norm should be of lower priority.